2023
DOI: 10.1177/17571774231158782
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of healthcare workers to COVID-19 infection prevention practices and its relationship with SARS-CoV-2 seropositivity

Abstract: Background Infection prevention and control (IPC) practices against COVID-19 should be adopted by healthcare workers (HCWs) at their workplaces to protect themselves, their patients, and their families from infection. Purpose This study aimed to describe the relationship between the healthcare-related COVID-19 infection prevention measures adopted by HCWs and their SARS-CoV-2 seropositivity. Research Design This cross-sectional study was conducted during the second and third COVID-19 waves in Egypt. Study Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…9 It is reported that poor infection control measures were linked to SARS-CoV-2 seropositivity among HCWs during the second and third COVID-19 waves. 10 The study conducted in Al Riyadh, Saudi Arabia, uncovered that 80.2% of healthcare workers (HCWs) demonstrated good infection control practices in hospitals, a rate lower than estimates in other locations. This finding highlights significant regional variations in infection control practices (ICP) (1).…”
Section: Introductionmentioning
confidence: 99%
“…9 It is reported that poor infection control measures were linked to SARS-CoV-2 seropositivity among HCWs during the second and third COVID-19 waves. 10 The study conducted in Al Riyadh, Saudi Arabia, uncovered that 80.2% of healthcare workers (HCWs) demonstrated good infection control practices in hospitals, a rate lower than estimates in other locations. This finding highlights significant regional variations in infection control practices (ICP) (1).…”
Section: Introductionmentioning
confidence: 99%